The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11064-015-1560-y
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic Effects of Mu Bie Zi (Momordica cochinchinensis) Seed Elucidated by High-Throughput Screening of Natural Products for NGF Mimetic Effects in PC-12 Cells

Abstract: Post-mitotic central nervous system (CNS) neurons have limited capacity for regeneration, creating a challenge in the development of effective therapeutics for spinal cord injury or neurodegenerative diseases. Furthermore, therapeutic use of human neurotrophic agents such as nerve growth factor (NGF) are limited due to hampered transport across the blood brain barrier (BBB) and a large number of peripheral side effects (e.g. neuro-inflammatory pain/tissue degeneration etc.). Therefore, there is a continued nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…The findings in this study corroborate our previous finding in that the seed also contains a neuritogenic factor [ 19 ], further classified as a protein or peptide having a mass of 17 kDa. Given the lack of annotation for the Momordica cochinchinensis proteome, identification of proteins was limited to that previously sequenced confirming some sequences similar to the highly ubiquitous 11S globulin and napin seed storage proteins, oleosin, and specific Momordica genus cyclotides: trypsin inhibitors I (MCoTI-I), 2 (MCoTI-II), and TIPTOP proteins.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings in this study corroborate our previous finding in that the seed also contains a neuritogenic factor [ 19 ], further classified as a protein or peptide having a mass of 17 kDa. Given the lack of annotation for the Momordica cochinchinensis proteome, identification of proteins was limited to that previously sequenced confirming some sequences similar to the highly ubiquitous 11S globulin and napin seed storage proteins, oleosin, and specific Momordica genus cyclotides: trypsin inhibitors I (MCoTI-I), 2 (MCoTI-II), and TIPTOP proteins.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, in a discovery-based approach, we screened over an 1100 food/plant-based product to determine if any of these could elicit basic neurite outgrowth in PC-12 cells to an extent similar to NGF. We elucidated the seed of Mu Bie Zi , Momordica cochinchinensis, while finding no mimetic effects in the fruit [ 19 ]. In the current study we explore the biological nature of constituents responsible for neuritogenic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Seow et al (13) suggested that 6-shogaol, a compound derived from ginger (Zingiber officinale var officinale), induced neurite outgrowth. In another study, Momordica cochinchinensis seed displayed NGF-mimetic activity and induced neurite outgrowth in PC-12 cells (14). Moreover, the neuronal differentiation effect of growth factors has been extensively studied.…”
Section: Introductionmentioning
confidence: 98%
“…Previously, we discovered that an extract of the seed of the Momordica cochinchinensis exerted neurotrophic, NGF mimetic effects in PC-12 cells . While the molecular basis of this effect remains to be determined, the cystine-knot motif of NGF put us in mind of the MCoTI plant defense proteins, which similarly contain a cystine knot and also could bind with high affinity to Family S1 serine endopeptidases. MCoTI-I and -II are found in the M.…”
Section: Introductionmentioning
confidence: 99%